Deconstructing Masculinity in the Clothing Representation of Ghibli Anime Characters by the TikTok Account @Delvinyauu (A Roland Barthes Semiotic Study on Japanese Popular Culture in Indonesia) - Rahmasari, RIfka Firzanah (representamen, 2024)
This research explores the representation of masculinity in TikTok content by the creator @Delvinyauu, focusing on the portrayal of characters from Studio Ghibli films. It investigates how these representations challenge traditional masculine stereotypes in Japanese culture, particularly through the lens of soft masculinity. Utilizing a descriptive qualitative method combined with Roland Barthes' semiotic analysis, the study analyzes the denotative and connotative meanings behind fashion choices, body language, and character portrayals. Results indicate that the creator's content resonates with audiences, showcasing a softer, empathetic masculinity that diverges from conventional ideals. This shift promotes a more nuanced understanding of masculinity, encouraging emotional expression and individuality in contemporary society. The study concludes that TikTok serves as a platform for redefining masculine identity, as it reflects the evolving perceptions of gender roles among youth in Indonesia.